Effect of density of surface defects on photoluminescence properties in MAPbI3 perovskite films - Faßl, Paul; Zakharko, Yuriy; Falk, Lukas M.; Goetz, Katelyn; Paulus, Fabian; Taylor, Alexander D.; Zaumseil, Jana; Vaynzof, Yana (Journal of materials chemistry. C, Materials for optical and electronic devices, 2019)
In this work we investigate the effect of tuning the density of surface defects of methylammonium lead triiodide (MAPbI3) perovskite films on their photoluminescence (PL) properties. Control over the density of defects is achieved by fractionally changing the perovskite precursor stoichiometry, which results in a gradual change in the I− and MA+ vacancy/interstitial densities. PL spectroscopy studies reveal that an increase in stoichiometry results in both a lower initial PL and a lower enhancement upon exposure to light in the ambient environment. Confocal PL microscopy and time resolved studies show that the heterogeneity in emission properties across the samples is also closely related to the spatial distribution of the density of surface defects. Our results show that while the overall density of defects dictates the initial PL, it is the density of shallow defects that determines the evolution of the PL with time.
Im Titel ist die Zahl "3" tiefgestellt
Gesehen am 19.08.2019